A Qualitative Policy Analysis of the Trump 2.0 Universal Tariff - Sabila, Alana (Journal of Entrepreneurship & Business, 2025)
Purpose: The United States’ April 2025 “Trump 2.0” order— combining a blanket 10 percent tariff with country-specific “reciprocal” surcharges—represents the largest single expansion of U.S. protectionism since the 1930s. For Indonesia, the measure imposes a 32 percent duty on its exports, threatening one tenth of merchandise sales and large segments of Java’s labour-intensive manufacturing. This study provides an early-stage qualitative policy analysis of the shock. Method: A triangulated research design integrates: (i) comparative historical review of past U.S. tariff waves; (ii) desk analysis of high- frequency customs and freight data through March 2025; and (iii) input–output tracing with the 2021 Indonesian Supply–Use Table to assess import-content vulnerability. Result: Findings indicate a first-year export shortfall of ~USD 1 billion (0.3 % of GDP), with 55 % of exposure concentrated in HS 85 electrical machinery, HS 61–62 apparel, and HS 64 footwear. A 10 % rupiah depreciation would raise production costs by 4.7 % in West Java electronics and 3.2 % in Central Java garments, given import coefficients of 0.47 and 0.32. Indirect spillovers are significant: China and ASEAN supply 65 % of Indonesia’s intermediate imports and are discounting diverted components, threatening assembly-line utilisation below the 85 % shutdown threshold. Policy resilience requires a five-point package: surplus-management diplomacy, selective MFN concessions on U.S. capital goods, accelerated Asia– Africa market diversification, safeguards against diversion imports, and coordinated macro-financial support for export-oriented SMEs. Future research should combine post-implementation customs data with firm-level panels to measure household income effects and evaluate mitigation efficacy.